2016
DOI: 10.1002/j.0022-0337.2016.80.1.tb06057.x
|View full text |Cite
|
Sign up to set email alerts
|

Access to Interpreter Services at U.S. Dental School Clinics

Abstract: The number of Americans with limited English proiciency (LEP) is growing, and legal protections mandate that LEP individuals have equal access to health care services. The aim of this study was to determine the availability of interpretation services in U.S. dental school clinics and the kinds of instruction dental students are given regarding treatment of LEP patients. A survey was distributed to the academic deans of all U.S. dental schools; 35 completed the survey for a response rate of 58%.Respondents were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
10
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 32 publications
(37 reference statements)
3
10
1
1
Order By: Relevance
“…This result is consistent with the findings of Simon et al, who reported in 2017 a similar lack of confidence among students in working with patients who are LEP, even at graduation 12 . Additionally, like most schools in Simon et al's study published in 2016, 13 Minnesota's formal instruction in working with interpreters is presented briefly in a lecture format related to cultural competence and social determinants of health. Students reported they traditionally relied on informal experience in the school clinics to develop actual patient‐provider‐interpreter communication skills.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This result is consistent with the findings of Simon et al, who reported in 2017 a similar lack of confidence among students in working with patients who are LEP, even at graduation 12 . Additionally, like most schools in Simon et al's study published in 2016, 13 Minnesota's formal instruction in working with interpreters is presented briefly in a lecture format related to cultural competence and social determinants of health. Students reported they traditionally relied on informal experience in the school clinics to develop actual patient‐provider‐interpreter communication skills.…”
Section: Discussionsupporting
confidence: 89%
“…Using an action research approach to design, the project team created a rich and meaningful learning experience to develop fundamental skills in working with interpreters and patients who are LEP. This highly interactive, three‐hour, skills‐based workshop stands in contrast to Simon et al's finding that written resources and informational lectures were the most commonly used methods in dental schools for this kind of instruction 13 …”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…LEP individuals tend to have lower income and poorer oral health [24]. Previous research has indicated that dental schools may see more LEP patients than the national average [25]. Interestingly, in this study, the proportion of patients with LEP seen in the teaching practice, 7.97%, was found to be lower than the proportion of Massachusetts residents with LEP, 8.8% [26].…”
Section: Discussioncontrasting
confidence: 52%
“…Однако конституция регламентирует их равный с коренными жителями доступ к медицинской помощи. В связи с большим наплывом таких пациентов в клиниках стоматологических школ у стоматологов-студентов возникают определенные трудности [31,32]. Установлено, что подобные больные получают меньше внимания и худшее лечение, хотя имеют более низкие показатели здоровья, чем пациенты, у которых английский язык родной.…”
unclassified